Badania marketingowe we wprowadzaniu produktów na rynki europejskie - Ratajczyk, Piotr (Marketing Research in Product Introduction on European Markets, 2006)
The product introduction and modification process is a crucial and inherent element of a company's activity. The level of difficulty is raised in the case of foreign markets. Except basic element we are forced to take into consideration many other factors which can influence the research process and further - product success. The aim of the consideration is to underline the elements which have to be additionally detailed through the analyses.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1107, s. 200-205